Risk-Return Measures of Ex Post Portfolio Performance - Smith, Keith V.; Tito, Dennis A. (Journal of Financial and Quantitative Analysis, 1969)
Risk continues to be a widely discussed topic within the field of finance. Academicians add risk variables to their quantitative models, while financial practitioners include risk considerations in their qualitative deliberations. In both contexts, risk — together with some measure of profit or return — generally comprise a dual or composite criteria for investment decision-making purposes. Whereas the decisionmaking situation can be described as ex ante, this article deals with risk in an ex post context. In particular, it reports an investigation of alternative risk-return measures which are designed to rank and evaluate the ex post performance of investment portfolios. Section I reviews three composite measures of performance and examines their interrelationships. A fourth alternative measure is also suggested. In Section II, the measures are used to rank the portfolio performance of a sample of mutual funds. Some difficulties in making performance comparisons of these funds against the market are discussed in Section III. The final section briefly explores the implications of the study and suggests areas for subsequent research.